2015
DOI: 10.1021/am5090385
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Thermal Stability and Lifetime of Solid-State Dye-Sensitized Solar Cells via Molecular Engineering of the Hole-Transporting Material Spiro-OMeTAD

Abstract: Thermal stability of hybrid solar cells containing spiro-OMeTAD as hole-transporting layer is investigated. It is demonstrated that fully symmetrical spiro-OMeTAD is prone to crystallization, and growth of large crystalline domains in the hole-transporting layer is one of the causes of solar cell degradation at elevated temperatures, as crystallization of the material inside the pores or on the interface affects the contact between the absorber and the hole transport. Suppression of the crystal growth in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
316
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(340 citation statements)
references
References 63 publications
9
316
2
1
Order By: Relevance
“…We note that the glass transition temperature of Z1011 is 24 °C higher than spiroOMeTAD, which retards the formation of crystalline domains within the hole-transporter layer during device aging. [38,39] Moreover, preliminary test ( Figure S7, Supporting Information) shows that the Z1011-based device is more resistant to heat stress than the device based on spiro-OMeTAD at 80 °C.…”
Section: Doi: 101002/aenm201600401mentioning
confidence: 99%
“…We note that the glass transition temperature of Z1011 is 24 °C higher than spiroOMeTAD, which retards the formation of crystalline domains within the hole-transporter layer during device aging. [38,39] Moreover, preliminary test ( Figure S7, Supporting Information) shows that the Z1011-based device is more resistant to heat stress than the device based on spiro-OMeTAD at 80 °C.…”
Section: Doi: 101002/aenm201600401mentioning
confidence: 99%
“…Malinauskas et al argued that the fully symmetrical spiro-MeOTAD tends to be easily crystallized, which can affect the contact between the perovskite and the HTM [35]. Local asymmetry was introduced into the spiro-MeOTAD to suppress the crystal growth.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…However, it is known that spiro-OMETAD causes degradation in the devices performance and the field is still research active (Nogueira et al, 2004;Pudzich et al, 2006). There is some published work dedicated to the HTM layer and its effect on the stability of perovskite solar cells (PSC) (Malinauska et al, 2015;Badia et al, 2014;Nguyen et al, 2014). There is also a reasonable literature on the degradation of the performance of Dye Sensitized cell (DSC) due to the use of spiro-OMETAD O'Brien et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It is reasonable to expect that the same conclusions apply to PSC as the reported issues are highly associated with the spiro-OMETAD itself. These issues are mainly related to the thermal stress effects (Malinauska et al, 2015;Bailie et al, 2014;O'Brien et al, 1998) and oxidization effects (Badia et al, 2014;Nguyen et al, 2014). Additionally, Snaith et al reported recently TiO 2 -free device that showed stability of the photocurrent over 1000 h of exposure to simulated sunlight .…”
Section: Introductionmentioning
confidence: 99%